2021
DOI: 10.18699/vj21.033
|View full text |Cite
|
Sign up to set email alerts
|

Lack of GAGA protein in Trl mutants causes massive cell death in Drosophila spermatogenesis and oogenesis

Abstract: Drosophila protein GAGA (GAF) is a factor of epigenetic transcription regulation of a large group of genes with a wide variety of cellular functions. GAF is encoded by the Trithorax-like (Trl) gene, which is important for the formation of various organs and tissues at all stages of ontogenesis. In our previous works, we showed that this protein is necessary for the development of the reproductive system, both in males and females of Drosophila. Decreased expression of the Trl gene led to multiple disorders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 59 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Lack of GAGA in testes leads to death and degradation of germline cells ( Dorogova et al, 2021 ). The question we wanted to answer in this project is whether GAGA is a transcriptional regulator of cell death in Drosophila testes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lack of GAGA in testes leads to death and degradation of germline cells ( Dorogova et al, 2021 ). The question we wanted to answer in this project is whether GAGA is a transcriptional regulator of cell death in Drosophila testes.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we demonstrated that autophagosomes and lysosomes are abundant in the cytoplasm of dying spermatocytes. Nevertheless, the death of these cells does not involve apoptosis ( Dorogova et al, 2021 ). Here, we analyzed the genes belonging to the “autophagy” (GO:0006914) and “lysosome” (GO:0005764) FlyBase terms ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations